Stresses in the plantar region for long- and short-range throws in women basketball players - Pau, M.; Ciuti, C. (European Journal of Sport Science, 2013)
This study aimed to assess plantar pressure pattern modifications caused by short- and long-distance shots in women basketball players. To this end, 24 experienced national- and regional-level basketball players performed 3 trials of 4 technical gestures (free throw, jump stop shot, three-point shot and lay-up) barefoot on a pressure platform placed in fixed positions on the court. Raw data were processed to calculate location and magnitude of pressure peaks in three sub-regions (forefoot, midfoot and rearfoot), and the increase ratio was calculated relative to plantar pressure measured during a static bipedal and unipedal upright stance. The results showed significant increases (p<0.001) in plantar pressure peaks in forefoot (but not midfoot and rearfoot) for all the gestures that involved the use of both legs. Particularly large increases were detected for the three-point shot. All three sub-regions underwent significant changes of the pressure peak in the case of lay-up (forefoot and rearfoot: p<0.001, midfoot: p=0.002). The high levels of contact stress detected for routinely performed technical gestures suggest that a detailed knowledge of changes in the physiological patterns of plantar stresses that take place during play is crucial in reducing the risk of foot injuries and establishing proper training and rehabilitation protocols.